The effect of giving blood supplement tablets to adolescent girls on increasing haemoglobin levels in Cirebon District to prevent stunting and develop a quality generation in Cirebon District - Vianty Mutya Sari; Siti Difta Rahmatika; Wiwin Widayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background : Several conditions that affect adolescent health, including adolescent reproductive health are nutritional problems. Nutritional problems that occur in adolescents include anemia and chronic lack of energy. Anemia is a decreasing quantity of red blood cells in the circulation or the amount of haemoglobin under normal limits. The challenge of anemia in young women from 37.1% in Riskedas 2013 which actually increased to 48.9% in Riskesdas 2018, with the proportion of anemia in the age group 15-24 years and 25-34 years. These things clearly reinforce that adolescent health will determine the success of health development, especially in an effort to print the quality of the nation's next generation in the future. Anemia among adolescents can be caused by a lack of macronutrient and micronutrient intake. The micronutrients are needed by the body, especially by teenagers. Insufficiency of micronutrients in the body can cause anemia. Anemia has several types, one of which is nutritional anemia. One of the causes of nutritional anemia is iron deficiency. Based on Permenkes, RI No. 88, 2014, giving blood supplement tablets is one of the important efforts in the prevention and control of anemia because it is an effective way to prevent anemia due to iron deficiency and folic acid deficiency. Blood supplement tablets are tablets that are given to the fertile and pregnant women. For fertile women, it is given once in a week and once a day during period. Purpose : To determine the effect of giving blood supplement tablets to adolescent girls to increase hemoglobin levels, so, it can be seen whether female adolescents are anemic or not. If there are many adolescents with anemia, it is expected that health workers and the community should pay more attention to the importance of anemia-free of adolescents to prevent stunting. Therefore, there many healthy generations born in Cirebon .Method : This study uses a quasi-experimental design, where there is a treatment of giving blood supplement tablets for 3 months to junior high school students who have experienced menstruation whose hemoglobin levels were previously checked. After giving blood tablets for 3 months, the hemoglobin level was rechecked which involved 20 female students at Cirebon district. Result : The average of haemoglobin levels before given the treatment was 11.40 grams% with a standard deviation of 1.7634. Meanwhile the average of haemoglobin levels after given the treatment was increased 2.67 grams% to 14.07 grams% with a standard deviation of 1.3719. The result of statistical tests using the Dependent T test, p=0,000, means at 5% alpha, the final hypothesis accepted. There is a significant difference in haemoglobin levels before and given the treatment (giving the blood supplement tablet). This means there is an effect of giving the blood supplement tablets to adolescent girls on increasing haemoglobin levels. Conclusions : There is an effect of giving blood supplement tablets to adolescent girls on increasing haemoglobin levels.